Extracellular vesicle-derived lncRNA VIM-AS1 promotes diabetic wound healing by promoting glycolysis and alleviating cellular senescence - Feiyuan Liang; Nanchang Huang; Yu Tian; Yuqi Fang; Chuangming Huang; Boyuan Qiu; Tiantian Lu; Li Zheng; Jianwen Cheng; Bo Zhu; Jinmin Zhao (Stem Cell Research & Therapy)
Abstract Aims Diabetic wound healing is a significant challenge due to impaired cellular functions, and current therapeutic approaches often prove inadequate. This study aims to explore the role of extracellular vesicles (EVs) derived from human umbilical mesenchymal stem cells (HuMSCs), particularly focusing on their associated long non-coding RNAs (lncRNAs), in promoting diabetic wound repair. Methods To investigate this, we employed lncRNA sequencing of EVs, created reprogrammed EVs, and utilized a diabetic rat  model. The impact of HuMSCs-derived EVs on fibroblast glycolysis, proliferation, and migration was assessed, along with the function of lncRNA VIM-AS1 in glucose metabolism via the PPAR-γ pathway. Results Our results demonstrate that HuMSCs-derived EVs enhance glycolysis in fibroblasts, which is essential for effective wound healing. We identified lncRNA VIM-AS1 as a pivotal regulator that not only promotes fibroblast proliferation and migration but also significantly enhances endothelial cell function, specifically regarding angiogenesis and tissue vascularization. Furthermore, EVs-derived lncRNA VIM-AS1 was found to reduce reactive oxygen species (ROS) levels, thereby mitigating oxidative stress and cellular senescence in both fibroblasts and endothelial cells. In vivo experiments in rat models confirmed the capacity of EVs-derived lncRNA VIM-AS1 to improve diabetic wound healing. Conclusions This study highlights the therapeutic potential of HuMSCs-derived EVs and specifically lncRNA VIM-AS1 as innovative approaches to address the challenges of tissue repair in diabetic conditions, offering promising strategies for enhancing wound healing efficacy.